Infrastruktur Dan Pertumbuhan Ekonomi Di Indonesia - Laili Faridatun Nasikhah; Susilowati, Dwi (Jurnal Ilmu Ekonomi JIE, 2024)
The research aims to determine the influence of population, investment, and infrastructure on economic growth in Indonesia. This research was conducted in Indonesia, namely Indonesia, from 1991-2021. This research uses secondary data in the form of time series data. Secondary data used in this research are population, investment, infrastructure, and GDP. The population used is Indonesia. The sample used is the 1991-2021 period. Data collection techniques using time series data obtained from the World Bank. This research uses multiple linear regression. This research shows a positive and significant influence between the population variable and economic growth in Indonesia. In contrast, the investment variable has a positive and insignificant influence on economic growth in Indonesia. And infrastructure has a positive and significant effect on economic growth in Indonesia.